2020
DOI: 10.3390/ijms21062237
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Activity and Expression of Cyclooxygenases COX1 and COX2 in THP-1 Monocytes and Macrophages Cultured with BiodentineTM Silicate Cement

Abstract: BiodentineTM is a material based on hydrated calcium silicate with odontotropic properties. However, from the clinician’s perspective, every material used to fill a tooth—even those showing the optimal biochemical parameters—is in fact a foreign body introduced to the organism of the host. Therefore, apart from the chemical parameters of such materials, equally important is the so-called biocompatibility of such materials. The aim of the study was to investigate whether BiodentineTM, used in the regeneration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
2
4
1
Order By: Relevance
“…With respect to BD, the present study showed that it led to significantly higher stimulation of the monocytes and subsequent release of cytokines in comparison with other groups. Such finding contrasts with previous results from in vitro study (Barczak, Palczewska‐Komsa, Lipski, et al, 2020; Barczak, Palczewska‐Komsa, Nowicka, et al, 2020). In vivo studies showed that BD resulted in adequate biological response, that is as similar as to MTA.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…With respect to BD, the present study showed that it led to significantly higher stimulation of the monocytes and subsequent release of cytokines in comparison with other groups. Such finding contrasts with previous results from in vitro study (Barczak, Palczewska‐Komsa, Lipski, et al, 2020; Barczak, Palczewska‐Komsa, Nowicka, et al, 2020). In vivo studies showed that BD resulted in adequate biological response, that is as similar as to MTA.…”
Section: Discussioncontrasting
confidence: 99%
“…In respect to MTA, the present study showed that it was associated with significantly lower levels of inflammatory cytokines released by monocytes compared to Biodentine. Comparable findings were previously reported in an in vitro study where MTA product did not trigger THP‐1 Macrophages to release inflammatory mediators (Barczak, Palczewska‐Komsa, Lipski, et al, 2020; Barczak, Palczewska‐Komsa, Nowicka, et al, 2020). Contrasting results were found by another in vitro study where they found that MTA can trigger the release of pro‐inflammatory molecules namely IL‐1β, TNF‐α and IL‐6 by RAW 264.7 macrophages (Yuan et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…For THP-1 cells, our data showed the successful differentiation of these monocytes into macrophages based on the cell surface markers' expression as analyzed by flow cytometry, and these results are in alignment with a previous study [34]. Macrophages are important innate immune cells that are associated with two distinct types: a proinflammatory subset M1with prototypic macrophage functions such as inflammatory cytokine production and bactericidal activity and an anti-inflammatory subset M2 linked with wound healing and tissue repair processes [35].…”
Section: Biomed Research Internationalsupporting
confidence: 89%
“…Shi et al, 2014 compared cytotoxic activity of iRoot BP Plus and MTA ProRooton human gingival fibroblasts in medium in vitro and evaluated the cells vitality. The results obtained in the aforementioned study demonstrate that cell vitality at different concentrations of iRoot BP Plus and MTA amounted to from 77.3% to 113.8% with no cytotoxic effects recorded in either of the materials [ 37 ].…”
Section: Discussionmentioning
confidence: 99%